146k views
4 votes
Factor completely. x8 - 1/81

User ABlaze
by
5.2k points

1 Answer

4 votes

Answer:

((3 x^2 - 1) (3 x^2 + 1) (9 x^4 + 1))/81

Explanation:

Factor the following:

x^8 - 1/81

Put each term in x^8 - 1/81 over the common denominator 81: x^8 - 1/81 = (81 x^8)/81 - 1/81:

(81 x^8)/81 - 1/81

(81 x^8)/81 - 1/81 = (81 x^8 - 1)/81:

(81 x^8 - 1)/81

81 x^8 - 1 = (9 x^4)^2 - 1^2:

((9 x^4)^2 - 1^2)/81

Factor the difference of two squares. (9 x^4)^2 - 1^2 = (9 x^4 - 1) (9 x^4 + 1):

((9 x^4 - 1) (9 x^4 + 1))/81

9 x^4 - 1 = (3 x^2)^2 - 1^2:

((3 x^2)^2 - 1^2 (9 x^4 + 1))/81

Factor the difference of two squares. (3 x^2)^2 - 1^2 = (3 x^2 - 1) (3 x^2 + 1):

Answer: ((3 x^2 - 1) (3 x^2 + 1) (9 x^4 + 1))/81

User Juny
by
4.9k points